2018
DOI: 10.1016/j.vaccine.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and practices about influenza vaccination among pregnant women and healthcare providers serving pregnant women in Managua, Nicaragua

Abstract: Background Nicaragua implemented an influenza vaccination program for pregnant women with high-risk obstetric conditions in 2007. In 2014, the recommendation of influenza vaccination expanded to include all pregnant women. Given the expansion in the recommendation of vaccination, we evaluated knowledge, attitudes and practices of pregnant women and their healthcare providers towards influenza vaccination and its recommendation. Methods We conducted surveys among pregnant women and their healthcare providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…The majority of studies with quantitative results for the pertussis vaccine had investigated intention to be vaccinated rather than actual vaccination status. Pregnant women who had received an HCP recommendation had 12-times higher odds of accepting seasonal influenza vaccination (OR 12.02, 95% CI 6.80–21.23, 21 studies, 14,099 women) [ 21 – 41 ] and 10-times greater odds of accepting pertussis vaccine (OR 10.33, 95% CI 5.49–19.43, 2 studies, 637 women) [ 27 , 29 ] compared to those who had not received recommendations. For pandemic vaccine the recommendation increased the odds of antenatal H1N1 vaccine uptake by six times (OR 6.76, 95% CI 3.12–14.64, 5 studies, 6898women) [ 42 46 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies with quantitative results for the pertussis vaccine had investigated intention to be vaccinated rather than actual vaccination status. Pregnant women who had received an HCP recommendation had 12-times higher odds of accepting seasonal influenza vaccination (OR 12.02, 95% CI 6.80–21.23, 21 studies, 14,099 women) [ 21 – 41 ] and 10-times greater odds of accepting pertussis vaccine (OR 10.33, 95% CI 5.49–19.43, 2 studies, 637 women) [ 27 , 29 ] compared to those who had not received recommendations. For pandemic vaccine the recommendation increased the odds of antenatal H1N1 vaccine uptake by six times (OR 6.76, 95% CI 3.12–14.64, 5 studies, 6898women) [ 42 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant women who received a seasonal influenza vaccination during a prior pregnancy had nine-times higher odds of accepting a pandemic influenza vaccine in their current pregnancy than those who did not vaccinate in a prior pregnancy (OR 9.12, 95% CI 1.99–41.76, 2 studies, 442 women) [ 43 , 53 ]. There was no evidence to suggest an association between prior maternal vaccination and season influenza vaccinations (OR 1.51, 95% CI 0.71–3.24, 3 studies, 2,339 women) [ 21 , 22 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All 17 countries have received technical and/or financial support for program and/or policy development and evaluation (Table 1). KAPP surveys about influenza and vaccination have been conducted or are planned for 2019 in 16 countries with the first work occurring in Lao PDR [20]. These surveys focused on vaccine target groups, including health workers (12), pregnant women and their providers (12), persons with chronic disease (3) or caretakers and providers of health care for children (1).…”
Section: Resultsmentioning
confidence: 99%
“…6 In countries where influenza vaccines are recommended for pregnant women, studies have identified health-care provider recommendation, referral, women's knowledge, attitudes and beliefs about influenza and influenza vaccine as important predictors of influenza vaccine acceptance among pregnant women, but available data are limited. [7][8][9][10][11][12][13][14] Understanding predictors of vaccination against influenza among pregnant women in low-and uppermiddle-income countries is important and may inform strategies for improving vaccine uptake in this population. Using data from a multi-country prospective cohort study conducted in a low middle-income country (India) and two upper middlecountries (Peru and Thailand, Table 1), 15 we assessed what factors were associated with influenza vaccination among CONTACT Carmen S. Arriola wus3@cdc.gov Influenza Division, Centers for Disease Control and Prevention, Atlanta, GA 30329, USA.…”
Section: Introductionmentioning
confidence: 99%